DIGITALISASI UMKM DAN PELESTARIAN DESA WISATA DI DESA GURAH KABUPATEN ACEH BESAR - Susanti, Susanti; Syaifuddin Yana; Maryam, Maryam; Nelly, Nelly; Radhiana, Radhiana; Marlina, Marlina; Alfi Sidqi (Yayasan Nusantara Hasana Berdikari, 2025)
The National Community Service (PKM) program in Gurah Village, Aceh Besar, was a collaboration between the Faculty of Economics, Serambi Mekkah University, the village government, students, and other stakeholders. The program aimed to strengthen, community capacity, encourage the digitalization of MSMEs, engage students as agents of change, foster environmental awareness, and build cross-university networks. The series of activities included an official opening, the signing of an MoU, a handover of student PPK Ormawa (Student Organizations), cybersecurity training, red shoot planting, and an interactive discussion. This activity provided tangible benefits to the village community, MSMEs, students, universities, and the local government, including improving digital literacy, developing tourism villages, and strengthening partnership networks. The implementation results demonstrated that the National PKM can serve as a model for empowerment based on local wisdom that is inclusive, sustainable, and replicable in other regions.